Analysis of community understanding of Islamic inheritance management institutions in Malaysia / Khairul Anam Naqiuddin Muhamad and Azri Bhari - Muhamad, Khairul Anam Naqiuddin; Bhari, Azri (Academy of Contemporary Islamic Studies (ACIS), 2021)
The division of Islamic inheritance (faraid) is a ruling that has been stated through the verses of the Qur'an known as the verse of mawarith from surah an-Nisa 'is closely related to rights and responsibilities. Certainly, there are benefits and benefits to the economy and social wellbeing from the laws and regulations laid down by Allah S.W.T. The acceptance of Islamic law is well received and practiced in Malaysia by a legislature that specializes in Islamic law. However, in Islamic inheritance claims in Malaysia, there are a variety of agencies from different jurisdictions handling the administration and division of Islamic inheritance as a result of the legacy of the colonial legal system. This diversity of agencies and legislation leads to different procedures resulting in confusion and complexity in Islamic inheritance claims among the general public. The objective of this research is to describe the institutions involved in Islamic inheritance, to compare the functions between the institutions involved, and to analyse the community's understanding of the functions of Islamic inheritance institutions in Malaysia. The study was conducted using qualitative research, using library and observation methods to collect data. Next, the data were analysed using inductive, deductive and comparative methods on the topic material being discussed. The results of this study found that the various institutions involved in the management and administration of Islamic inheritance, through various written laws and different procedures that cause "confusion" among the public not only arise during the process of division and administration of the estate but also arises thereafter. An effective solution requires the existence of integrated legislative power, and clear institutions as well as uniform methods and procedures.